2003
DOI: 10.1093/treephys/23.13.931
|View full text |Cite
|
Sign up to set email alerts
|

High autumn temperature delays spring bud burst in boreal trees, counterbalancing the effect of climatic warming

Abstract: The effect of temperature during short-day (SD) dormancy induction was examined in three boreal tree species in a controlled environment. Saplings of Betula pendula Roth, B. pubescens Ehrh. and Alnus glutinosa (L.) Moench. were exposed to 5 weeks of 10-h SD induction at 9, 15 and 21 degrees C followed by chilling at 5 degrees C for 40, 70, 100 and 130 days and subsequent forcing at 15 degrees C in a 24-h photoperiod for 60 days. In all species and with all chilling periods, high temperature during SD dormancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
121
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(138 citation statements)
references
References 16 publications
15
121
2
Order By: Relevance
“…We then explored mean temperatures over a preforcing time window during the autumn/winter preceding the phenological event. For simplicity, this window is referred to as the chilling window, although the timing of this window could reflect temperatures that impact on phenology through a mechanism other than chilling, such as dormancy induction (Heide, 2003). We varied start dates (from ordinal day À120 up to the beginning of the forcing window in 2-day intervals) and durations (from 4 to 120 days in 2-day intervals) in all combinations.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We then explored mean temperatures over a preforcing time window during the autumn/winter preceding the phenological event. For simplicity, this window is referred to as the chilling window, although the timing of this window could reflect temperatures that impact on phenology through a mechanism other than chilling, such as dormancy induction (Heide, 2003). We varied start dates (from ordinal day À120 up to the beginning of the forcing window in 2-day intervals) and durations (from 4 to 120 days in 2-day intervals) in all combinations.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The action of these environmental drivers is complex and changes along the transition from a dormant to a non-dormant state. In addition, it has been shown that photoperiod and temperature interact at various stages during dormancy induction, release and quiescence (Håbjørg 1972, Junttila 1980, Heide 1993, 2003, Myking & Heide 1995, Partanen et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…In study I, the high temperatures encountered in late summer led to later growth cessation of shoot growth (in thermal time units) in the following summer, which is one mechanism of utilizing longer growing seasons. Furthermore, high autumn temperatures have resulted in later bud burst in the following spring with Betula and Alnus species, which could counterbalance the effect of warm springs that hasten bud burst (Heide 2003). …”
Section: Discussionmentioning
confidence: 99%